HIV prevalence among cervical (pre)cancer diagnoses in Suriname: a retrospective population study - Deborah Stijnberg; Regillio Charles; Mike Mc Kee; Mikel Chan; Antoon Grunberg; Ward Schrooten; Malti Adhin (Pan American Health Organization, 2024)
Objective. To determine the prevalence of HIV in women with (pre)cancerous cervical lesions in Suriname and their retention in care. Methods. A retrospective population study including all women diagnosed with (pre)invasive cervical intraepithelial neoplasia (CIN I to III or cervical cancer) in the only pathology department, during 2010-2020. The HIV test coverage and the HIV positivity ratio were determined through matching pathology data with the national HIV test database. The relation between retention in HIV care up to 2022 and different covariates was determined through Kaplan-Meier survival analysis and log-rank tests. Results. There were 2 901 (1 395 CIN I, 396 CIN II, 444 CIN III, and 666 cervical cancer) diagnoses of (pre)invasive cervical neoplasia. An overall HIV test coverage of 57.5% and a positivity ratio of 5.8% were found, with no difference among the (pre)cancer stages. The undiagnosed prevalence (women not previously known HIV-positive at cervical diagnosis) was 1.6% and 2.9% among precancer and cancer diagnoses, respectively. The median time in care of women with cervical cancer was 8 months for those not on antiretroviral therapy (ART) and 4 years for those starting ART. Among women with precancer stages this was 5 and 10 years, respectively (p < 0.05). Conclusions. HIV testing, followed by treatment initiation when found HIV-positive, should be prioritized in women diagnosed with cervical neoplasia. This will enhance the individual clinical outcomes and facilitate the control of the HIV epidemic in Suriname.